Long-Term Results of Darrach Resection in Patients 40 Years and Younger - Logli, Anthony L.; Strother, Courtney Carlson; Kakar, Sanjeev; Rizzo, Marco (Journal of Wrist Surgery, 2025)
The purpose of this study was to assess the long-term clinical and radiographic outcomes after distal ulna resection (Darrach procedure) in young adults.A retrospective chart review identified all adult patients who underwent Darrach resection at 40 years of age or younger and had a minimum of 5-year follow-up. Twenty-one patients (24 wrists) were available for final follow-up. Fifteen patients (16 wrists) returned for in-person evaluation, and seven patients (eight wrists) completed questionnaires by phone.Mean PRWE and QuickDASH scores were 32 and 34, respectively. The median visual analog scale at rest was 0 and 1 with activity. In 88% of cases, patients reported they would have the same surgery again. Of those who were employed preoperatively, 81% (13/16) returned to work, with all but one patient returning to their preoperative job. Radioulnar convergence occurred in all patients, but only three (23%) were symptomatic.The Darrach procedure may be a viable surgical option for DRUJ pathology in younger adults when other options are unavailable.Therapeutic IV.
Keywords: Darrach procedure; distal ulna resection; radioulnar convergence